2006
DOI: 10.1515/jpm.2006.031
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antenatal administration of vitamin K1 results in increasing the activities of vitamin K-dependent coagulation factors in umbilical blood and in decreasing the incidence rate of periventricular-intraventricular hemorrhage in premature infants

Abstract: Administration of vitamin K1 to pregnant women at less than 35 weeks' gestation age may result in improved coagulation and may reduce the incidence as well as the severity degree of PIVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Antenatal vitamin K was associated with a nonsignificant reduction in all grades of PVH (RR 0.82, 95% confidence interval (CI) 0.67-1.00) and in severe PVH (grades 3 and 4) (RR 0.75, 95% CI 0.45-1.25) for babies receiving prenatal vitamin K compared with control babies. In a subsequent RCT by Liu et al [251], 90 pregnant women in preterm labor at less than 35 weeks of gestation received vitamin K1 10 mg per day injection intramuscularly or intravenously for 2-7 days, or no such treatment. The overall rates of PVH were 32 and 52%, respectively (p=0.036), and the frequency of severe PVH was 5 and 20%, respectively (p=0.038).…”
Section: Resultsmentioning
confidence: 99%
“…Antenatal vitamin K was associated with a nonsignificant reduction in all grades of PVH (RR 0.82, 95% confidence interval (CI) 0.67-1.00) and in severe PVH (grades 3 and 4) (RR 0.75, 95% CI 0.45-1.25) for babies receiving prenatal vitamin K compared with control babies. In a subsequent RCT by Liu et al [251], 90 pregnant women in preterm labor at less than 35 weeks of gestation received vitamin K1 10 mg per day injection intramuscularly or intravenously for 2-7 days, or no such treatment. The overall rates of PVH were 32 and 52%, respectively (p=0.036), and the frequency of severe PVH was 5 and 20%, respectively (p=0.038).…”
Section: Resultsmentioning
confidence: 99%
“…describing alterations in the Vitamin K dependent coagulation system and subsequent risk of IVH [1,11,15,[17][18][19][20][21]. A recent study supports the assumption that this association seems to be influenced by genetic variants in genes linked to Vitamin K dependent coagulation [22].…”
Section: Several Studies Have Looked At Coagulation Tests and Subsequmentioning
confidence: 88%
“…One such example would be foetus/neonate. Trials looking at the efficacy of such therapy were initially promising [15,31], but the Cochrane review on this topic concluded that 'Vitamin K administered to woman prior to very preterm birth has not been shown to significantly prevent peri-ventricular haemorrhage in preterm infants or to improve neurodevelopmental outcomes in childhood' [32]. 8 We observed that there was some evidence that the early administration of blood products influenced the association between increased INR and increased risk of severe IVH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum osmolality, multiple births and cesarean section were not significantly correlated with the incidence of PIVH in premature infants. Maternal antenatal administration of vitamin K 1 or corticosteroids can significantly decrease the incidence of PIVH (13,14), and can be used routinely for women at risk of premature birth at <35 weeks of gestation. Antenatal supplementation with vitamin K 1 may significantly increase the plasma activities of factors II, VII and X, and consequently decrease the incidence of PIVH and lower the severity of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%